Teaching Students to be Political in a Nonpartisan Way: Reflections from Action Civics Education Across Red and Blue States. Issue 3 (27th May 2021) - Andes, Sarah; Fitzgerald, Jason C.; Cohen, Alison K.; Warren, Scott
ABSTRACT: Using a student-centered approach, Generation Citizen's (GC) action civics model helps students gain civic knowledge and skills as they work together to take action on a local issue in their community. This paper draws upon reflections from GC's decade-plus of teaching action civics at scale in middle and high schools across the United States, highlighting drivers for nonpartisan civics education efforts in Texas, Oklahoma, California, Alabama, Massachusetts, Rhode Island, and New York. Reflections on GC's work also point to the opportunities and challenges that GC encountered as it scaled We suggest future directions for research and practice for nonpartisan action civics work into the next decade.